P760 Sensitivity and specificity of the quantitative test for TPPA and RPR for diagnosis of congenital syphilis in neonates. (14th July 2019) - Gong, Xiangdong; Wu, Minzhi; Zhao, Liang
Abstract : Background: Diagnosis of congenital syphilis in neonates is difficult as TP-specific IgG can be passively transferred from mother to newborn, a reactive serologic test at birth does not necessarily indicate that the infant is infected. However, if the ratio of titer of TPPA or RPR for newborn-mother at delivery is more than 4 times, the neonate is considered to be infected with syphilis transmitted from mother. To date, it is not clear for sensitivity and specificity of the quantitative test for TPPA and RPR for diagnosis of congenital syphilis. Methods: Quantitative test for TPPA and RPR in 155 pregnant women with syphilis and their neonates were performed at delivery, and the infants were followed up by 18 months and TPPA was qualitatively tested. The positive of TPPA was considered as diagnosis for congenital syphilis at 18 months after birth. The ratio of titer of RPR or TPPA for newborn-mother was calculated, and their sensitivity and specificity were assessed for diagnosis of congenital syphilis. Results: 27 cases with congenital syphilis were diagnosed. The TPPA titer ratio of neonate-mother was greater than 4 times in 14 cases, of which 13 were patients with congenital syphilis. The sensitivity of TPPA titer ratio of neonate-mother for the diagnosis of congenital syphilis was 48.15%(95%CI: 29.30%–67.00%). The RPR titer ratio of neonate-mother was greater than 4 times in 7 cases, of which 6 were the patients with congenital syphilis. The sensitivity of RPR titer ratio of neonate-mother for the diagnosis of congenital syphilis was 22.22%(95%CI: 6.54%–37.90%). The sensitivity of combination of TPPA and RPR titer ratios for the diagnosis of congenital syphilis was 62.96%(95%CI: 44.75%–81.18%). The specificity of the two methods was 99.22%. Conclusion: The sensitivity of RPR or TPPA titer ratio of neonate-mother for the diagnosis of congenital syphilis was low, and the specificity was very high. Disclosure: No significant relationships.